The specificity of serum and local antibodies in female gonorrhoea. - Ison, C A (1986)
Immunoblotting has been used to compare the specificity of serum and local IgG and IgA antibodies in 13 women with gonorrhoea and in 13 controls. The technique allowed the simultaneous detection of antibodies to the major outer membrane proteins I, II, and III, pili and lipopolysaccharide; antibodies to another antigen which is probably a 'carbohydrate' were also detected. Serum and local IgG and IgA were found to be produced to several antigens during gonococcal infections, although the quantity of antibody was greater in serum. There was little change in the specificity of serum antibodies whereas the local response to LPS and pili increased over the two week study period. Serum antibody to LPS was more often IgG than IgA. Sera contained antibodies to 'carbohydrate', pili and lipopolysaccharide (LPS) whilst the local response was largely to the latter two antigens. Antibody to the outer membrane proteins was rarely detected. Control sera, but not vaginal washings, contained IgG and IgA to the major antigens but the staining of the immunoblots was less intense than those from patient's sera suggesting quantitative differences.